How the Service Provider Influences the Continuation of Physical Activity for People With Hip and Knee Osteoarthritis (Baltic Journal of Sport and Health Sciences, 2026)
Purpose: Osteoarthritis (OA) is the most common chronic condition in adults over 65 years old and affects over 528 million people worldwide (Vos et al., 2020). Physical activity plays a central role in managing OA-related pain, improving function, and supporting independent living. Structured programmes such as GLA:D® (Good Life with osteoArthritis from Denmark), which integrates exercise and education, have demonstrated significant short-term benefits (Baumbach et al., 2022). However, sustaining continued physical activity following the completion of these programmes remains a key challenge. Identifying the factors that support a successful transition from structured interventions to sustained, community-based activity is essential for fostering long-term self-management.Methods: This presentation reports preliminary findings from a systematic review exploring the barriers to and facilitators of physical activity maintenance in individuals with hip and knee OA. Six electronic databases (APA PsycInfo, CINAHL Complete, Cochrane Library, Embase, MEDLINE via PubMed, and Web of Science) were systematically searched using comprehensive Boolean terms. This sub-analysis focuses specifically on qualitative studies exploring the perspectives of service providers, as well as patient-reported experiences relating to provider influence.Results: Ten qualitative studies met inclusion criteria for this sub-analysis. Thematic analysis revealed several key themes across both patient and provider perspectives. From the patient viewpoint, three themes emerged: (1) Therapeutic alliance and person-centred education, highlighting the importance of trust and tailored information; (2) Ongoing support and accountability, referring to follow-up communication and provider encouragement; and (3) Collaborative goal-setting and empowerment, emphasising shared decision-making. From the provider perspective, three additional themes were identified: (1) Resource availability and constraints, such as limited access to resources; (2) Inclusive and supportive environments, such as attending local community-based classes; and (3) Promoting shared responsibility, where support is offered in a way that still promotes patient independence.Conclusion: These preliminary findings provide insight into the multifaceted role of service providers in supporting the maintenance of physical activity for individuals with OA. Understanding both patient and provider perspectives is essential in designing sustainable, community-based models of care. This sub-analysis contributes to a broader systematic review that will further explore the factors hindering sustained physical activity.